A utilização do uso de evidências científicas como política pública para a otimização na disponibilidade de vagas em UTI no Tocantins - Reis, Geovane Rossone (Universidade Federal do Tocantins, 2019)
The availability of vacancies in intensive care units in Tocantins has become a serious public health problem, on this level, Through the identification of studies and data collection of studies that resulted from the analysis of variables that generated better indicators of quality in intensive care, such as the reduction of length of stay, costs of care and mortality rate, with a view to explaining scientific and technocracy as a public policy for patient admission, and infection control as a direct or indirect way of guaranteeing a greater supply of ICU beds, this research was developed by analyzing data from patients hospitalized in public hospitals in the State of Tocantins, with the aim of to propose public policies based on scientific evidence in order to contribute to the optimization of vacancies in ICUs. This is a retrospective, quantitative and statistical documentary survey through correlation and data comparison, which were collected from patients hospitalized between January and December 2017 in the three main public ICUs in Tocantins, beginning with a systematic review of the literature sought scientific articles in Portuguese and English in the Medline, Cochrane, Capes journals portal, Latin American and Caribbean Center on Health Sciences Information - Bireme, Latin American and Caribbean Literature on Health Sciences - Lilacs and Scientific Electronic Library Online - Scielo. The data from this study showed a close relationship between the adoption of criteria for admission of patients and the control of infections in reducing length of stay, mortality rate and hospital costs. Evidence found in the results of this research shows that the application of evidence-based medicine in the management of public health policies, especially in intensive care units, can corroborate better quality indicators, with a greater supply of beds and, consequently, shorter waiting times , lower mortality rate and lower costs.